Faktor yang Mempengaruhi Kualitas Produk pada PT. XYZ - Widiyanti; Camila, Raden Firyal F; Masaki, Adilla Nastya; afitri, Wiji S (Apik Cahaya Ilmu, 2023)
Product quality is the main key to assessing the production performance of a company. To produce high-value product quality, there are several factors that need to be considered, such as the quality of raw materials, production processes, and labor quality. The purpose of this study is to test and analyze the effect of raw material quality, production process and labor quality on product quality at PT. XYZ. This type of research is quantitative. Where the population is all employees in the company, while the sample collected amounted to 50 people. The data collection technique for this study used questionnaires. The analysis method is in the form of data quality tests using validity and reliability test methods, classical assumption tests, multiple linear regression tests, as well as F tests and t tests for hypothesis testing. The results showed that the quality of raw materials, production processes, and the quality of labor together or simultaneously had a significant effect on product quality. Based on partial testing, it was found that the quality of products and the quality of ape power had a significant partial effect on the production process. Meanwhile, the production process does not have a significant partial effect on product quality. So, companies should pay more attention to SOPs in the company so that the products produced have much higher quality and high value.